2005
DOI: 10.4081/jlimnol.2005.153
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between anti-oxidant capacity and manganese accumulation in the soft tissues of two freshwater molluscs: Unio pictorum mancus (Lamellibranchia, Unionidae) and Viviparus ater (Gastropoda, Prosobranchia)

Abstract: Manganese is an element of great importance in the life cycle of plants and animals. For example, it plays an essential role as an activator of various enzymatic systems such as isoenzymes of superoxide dismutase. Freshwater Unionidae concentrate relatively large amounts of manganese in their tissues, but little is known about the physiological role of this metal. The aim of this research is to acquire a better knowledge of the role of manganese in molluscs which accumulate large amounts of this metal and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…Previous relevant scientific literature from this region was unfortunately based on incorrect taxonomy; for these studies, covering a range of scientific fields, including ecology (e.g. Ravera and Sprocati 1997;Ravera et al 2007), physiology (Campanella et al 2005;Carella et al 2016), toxicology (Guidi et al 2010;Polettini et al 2015;Sabbioni et al 2015), and aquaculture (Panini et al 2008;Sicuro et al 2010Sicuro et al , 2015, reanalysis using the taxonomy and distribution revealed in the present study might be necessary. For example, the study species of Ravera and Sprocati (1997), Ravera et al (2007), and Sicuro et al (2010) is U. elongatulus rather than U. mancus, which is only present in southern Italy, and when describing the host fishes of Anodonta cygnea, Giusti et al (1975) were not aware that three Anodonta species occurred in Trasimeno Lake instead of one.…”
Section: Discussionmentioning
confidence: 99%
“…Previous relevant scientific literature from this region was unfortunately based on incorrect taxonomy; for these studies, covering a range of scientific fields, including ecology (e.g. Ravera and Sprocati 1997;Ravera et al 2007), physiology (Campanella et al 2005;Carella et al 2016), toxicology (Guidi et al 2010;Polettini et al 2015;Sabbioni et al 2015), and aquaculture (Panini et al 2008;Sicuro et al 2010Sicuro et al , 2015, reanalysis using the taxonomy and distribution revealed in the present study might be necessary. For example, the study species of Ravera and Sprocati (1997), Ravera et al (2007), and Sicuro et al (2010) is U. elongatulus rather than U. mancus, which is only present in southern Italy, and when describing the host fishes of Anodonta cygnea, Giusti et al (1975) were not aware that three Anodonta species occurred in Trasimeno Lake instead of one.…”
Section: Discussionmentioning
confidence: 99%
“…Although much information is available (e.g . Pynnonen 1990;Gundacker 2000;Bonneris et al 2005;Campanella et al 2005), further research and more precise analysis on their physiology and ecology are needed to establish the status of freshwater molluscs as bioindicators of environmental stress.…”
Section: Isrmentioning
confidence: 99%
“…The M +2 is an important cofactor of mitochondrial superoxide dismutase, an antioxidant enzyme which scavenges oxygen free radicals [10]. It inhibits LPO produced by a free radical producing system, as potent antioxidant against oxidative stress at low doses [11]. Mn +2 supplementation reduced the leakage of lipids and phospholipid sperm contents under normal and induced oxidative stress conditions [12].…”
Section: Introductionmentioning
confidence: 99%